Characteristics of Pregnant Women with Thyroid Disorders at Wahidin Sudirohusodo Hospital Makassar - Hidayati, Prema Hapsari; Irmayanti; Fujiko, Masita; Erwin Rachman, Mochammad; Marendengi, Syafira Ananda (Gaceta Médica de Caracas, 2023)
Backgrounds: At least 2 %-3 % of pregnant women experience thyroid dysfunction, which affects the health of the mother and baby. There is still little research on pregnant women with thyroid disorders. Aim: Investigating the characteristics of pregnant women with thyroid disorders in Dr. Wahidin Sudirohusodo Hospital Makassar.